Системний та ситуаційний підходи як методологічна основа формування маркетингової стратегії екологізації аграрного виробництва - Багорка, Марія Олександрівна; Bagorka, Mariya (Національний авіаційний університет, 2017)
В статті визначена сутність, значення і основні принципи системного та ситуаційного підходів як методологічної основи при формуванні маркетингової стратегії екологізації агарного виробництва, а також представлена систематизація методів стратегічного аналізу для оцінки факторів середовища при формуванні маркетингової стратегії. Виділені основні причини, що обумовлюють системний підхід до використання методів при формуванні маркетингової стратегії екологізації. The transformations that are taking place in the agrarian sector today require expanding the study of the issues surrounding the formation of marketing activities in the agro-industrial complex, in particular, it concerns the development and implementation of methodological approaches in shaping the marketing strategy for environmentalizing agrarian production. The purpose of the study is to determine the essence, meaning and basic principles of system and situational approaches as a methodological basis for the formation of a marketing strategy for ecologization of agrarian production, as well as systematization of strategic analysis methods used to assess the environmental factors in the formation of this strategy.
System and situation approaches as methodological basis forming marketing strategy of agricultural production ecology
В статті визначена сутність, значення і основні принципи системного та ситуаційного підходів як методологічної основи при формуванні маркетингової стратегії екологізації агарного виробництва, а також представлена систематизація методів стратегічного аналізу для оцінки факторів середовища при формуванні маркетингової стратегії. Виділені основні причини, що обумовлюють системний підхід до використання методів при формуванні маркетингової стратегії екологізації. The transformations that are taking place in the agrarian sector today require expanding the study of the issues surrounding the formation of marketing activities in the agro-industrial complex, in particular, it concerns the development and implementation of methodological approaches in shaping the marketing strategy for environmentalizing agrarian production. The purpose of the study is to determine the essence, meaning and basic principles of system and situational approaches as a methodological basis for the formation of a marketing strategy for ecologization of agrarian production, as well as systematization of strategic analysis methods used to assess the environmental factors in the formation of this strategy. To select a well-grounded marketing strategy, you need to use a set of scientific approaches: systemic, situational and integration. The methodology of forming a marketing strategy for environmentalizing agrarian production is also based on a certain set of general scientific and applied methodical techniques. The development of a marketing strategy for the environmentalization of agrarian production is a rather complicated process based on a systematic approach. Situational approach is based on the fact that the formation of a marketing strategy for environmentalizing agrarian production is carried out on the basis of a particular market situation that has developed at one time or another. In our opinion, the basis of all applied marketing research methods is the strategic analysis of the industry, which undergoes the preparatory, analytical and final stages. It uses a number of specific methods and techniques that can diagnose the potential and existing threats of enterprises and industry, to identify their ability to formulate marketing strategies. The objective necessity of forming a marketing strategy for the environmentalization of agrarian production is related to the environmental problems of the agrarian sector, the urgent need for a stable food market, the provision of quality food products to the population and the efficient functioning of the agrarian sector of the economy. In the process of forming a marketing strategy for environmentalizing agrarian production system and situational approaches that underlie methods of strategic analysis are used. The basis of the systematic approach in forming the marketing strategy of ecologization of agrarian production are the mechanisms of its implementation, which ensure the stability of the system, its purposefulness; Interdependence, interdependence and complexity of its elements determines the integrity of the system; All tasks that execute individual elements of the system are interconnected; System elements and their associated actions have a certain subordination that builds hierarchy; The system changes under the influence of specific factors, which determines its dynamism; The ability of the system to adapt to the changing environment, without losing its own individuality.
Keywords: маркетингова стратегія екологізації; marketing strategy; аграрне виробництво; agrarian production; системний та ситуаційний підходи; system and situational approaches; стратегічний аналіз; strategic analysis; макро- і мікросередовище; macro-and micro-environment; інноваційний розвиток; innovative development